Polymers in microlithography : materials and processes - Reichmanis, Elsa, 1953-; MacDonald, Scott A.; Iwayanagi, Takao, 1949-; American Chemical Society. Division of Polymeric Materials : Science and Engineering (Washington, DC : American Chemical Society, 1989)
50